Pythagorean Picture Fuzzy Sets, Part 1- basic notions - Cuong, Bui Cong (Journal of Computer Science and Cybernetics, 2019)
Picture fuzzy set (2013) is a generalization of the Zadeh‟ fuzzy set (1965) and the Antanassov‟ intuitionistic fuzzy set. The new concept could be useful for many computational intelligent problems. Basic operators of the picture fuzzy logic were studied by Cuong, Ngan [10,11 ].New concept –Pythagorean picture fuzzy set ( PPFS) is a combination of Picture fuzzy set with the Yager‟s Pythagorean fuzzy set [12-14].First, in the Part 1 of this paper, we consider basic notions on PPFS as set operators of PPFS‟s , Pythagorean picture relation, Pythagorean picture fuzzy soft set. Next, the Part 2 of the paper is devoted to main operators in fuzzy logic on PPFS: picture negation operator, picture t-norm, picture t-conorm, picture implication operators on PPFS.As a result we will have a new branch of the picture fuzzy set theory.